Histological and histochemical studies of the sparganum of Spirometra ranarum (Meggitt, 1925) in Rana cancrivora Gravenhorst, 1829 - Rojanapaibul, Amnat (1979)
The histological structure and organization of the sparganum of spirometra ranarum are presented. The cuticle consists of three elements : the cuticular hair homogeneous basement and membrane. Immediately beneath is the subtegumentary masculature (peristaltic layer) arranged into outer circular and inner longitudinal layers; tranverse muscle fibers are distributed to the loosely packed parenchyma. The spongy parenchyma, with large cells and compact nuclei fill up all spaces nit filled up the fibro-muscular bundles , thick-walled excretory ducts, minute flame cells and nervous tissues, Gland like vacuolated cells are distributed in the entire length of the sparganum; laminated calcareous corpuscles are found throughout the sparganum except for one from the anterior and the invaginated region. The nerve bundles are noted near excretory ducts. Histochemical tests showed : 1. greatest concentration of glycogen in the muscle layers and parenchyma cells, less in the other subtegumentary cells and very slightly positive in the peripheral layer of the calcereous corpuscles in all regions; 2. the tegument and corpuscles reacted very strongly to Fischler's method for the posterior regions; 3. with the alkaline phosphates tests (Gamori, 1952, 1956) the calcareous corpuscles reacted very strongly, but slightly positive in the cuticle and the middle portion. The muscle layers at the middle and posterior regions had more acid phosphateses less in the tegument at the middle region and almost nil at the anterior region; 4. more concentration of acid mucopolysacharides in the parenchyma and less in the circular and longitudinal muscle at the anterior region; 5. The medullary parenchyma of the proliferative and growing areas of the anterior region reacted very strongly to the RNA (Methyl-green-pyromin) tes, less in the same structure at the middle region and longitudinal muscle layer in all regions; the slight reaction of the circular mucle layer in all regions including the medullary parenchyma at the posterior region indicate less proliferatibe activities.